Dampak free trade arrangements (FTA) terhadap ekonomi makro, sektoral, regional, dan distribusi pendapatan di Indonesia - Rina Oktaviani; . Widyastutik; Syarifah Amaliah (Institut Pertanian Bogor, 2010)
Indonesia's commitment to be involved in the scheme of Free Trade Agreement (FTA) is expected to bring a multiplier effect for the Indonesian economy, including sectoral, regional, and household distributional impact. The study was conducted using recursive dynamic Computable General Equilibrium Model (CGE) with further extension on top-down regional features. In the short term, the impact of the FTA has not seemed to significantly increase the national and regional GOP of each province. Trade liberalization scheme could potentially reduce the real income of households, the largest decline in low-income households in rural areas. Increased household income disparities need to be accounted with a serious community empowerment program to avoid social and economic conflicts. Increased competitiveness on regional and sectoral level is necessary. Improvement on market access is mandatory for several advantageous commodities. By increasing competitiveness, quality of infrastructures, and access to export markets, the export performance can beimproved. From the internal side, an efficient supply chain management is also crucial to meet the desires of consumers with quality, time, price and the right amount.